Palazzo Piccolomini - Martienssen, Rex D (Transvaal, Natal and Orange Free State Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1939)
'Rossellino made a model of the Rucellai. Of the Piccolomini he made a masterpiece."
Keywords: Palazzo Piccolomini; Martienssen Rex D; Rossellino, Bernardo; Renaissance facade elements; Palazzo Rucellai